Um Banco Central do Brasil independente: à procura de uma estrutura administrativa autônoma e descentralizada - Pitta de Santhiago, Maria das Graças (1994)
The dissertation is about the more adequate administrative structure for a central bank in search of its autonomy. First and second chapters deals with the current administrative situation of the Brazilian Central Bank (BACEN) and the dilemmas about its independence. In chapters 3 and 4, theoretical models of organizational structure and functional models of independent central banks are compared. Chapters 5 and 6 discuss the efforts that are actually done to make effective the autonomy of the BACEN, like the projects that are being treated by the National Congress and the BACEN's Strategic Action Plano These documents have been deeply analysed. The opinions of experts that are discussed in chapter 7 reinforce the concIusion that organizational changing for the Brazilian Central Bank autonomy is not only a consequence of technical, political and economic aspects, but of a wider process of integration between these and the behavioral and administrative variables of the organization.